12/15-Lipoxygenase choreographs the resolution of IgG-mediated skin inflammation. Issue 115 (December 2020) - Sezin, Tanya; Ferreirós, Nerea; Jennrich, Malin; Ochirbold, Khoroljav; Seutter, Malte; Attah, Claudia; Mousavi, Sadegh; Zillikens, Detlef; Geisslinger, Gerd; Sadik, Christian D.
Abstract: Autoimmune diseases are defined by an immune response against a specific autoantigen, driven by antigen-specific T cells or antibodies. While the mechanisms resolving brief episodes of acute inflammation elicited by microbial components or tissue injury are well understood, the mechanisms resolving tissue inflammation in autoimmune diseases are still largely elusive. We have, therefore, addressed the mechanisms of resolution in IgG-mediated autoimmune diseases using a mouse model of the pemphigoid disease "bullous pemphigoid-like epidermolysis bullosa acquisita" (BP-like EBA) as prototypical example. We found that 12/15-LO is induced in skin lesions of BP-like EBA and is predominantly expressed in eosinophils. Dependent on the expression of 12/15-LO, large amounts of proresolving lipid mediators, are biosynthesized in the skin by the point disease peaks. Their production is timely correlated to the gradual reversal of tissue inflammation. Genetic deficiency in Alox15, the gene encoding 12/15-LO, disrupts this process significantly protracting and aggravating disease. This protraction is associated reduced recruitment of regulatory T cells (Tregs ) into lesional skin. Intriguingly, Alox15 −/− mice also exhibit reduced recruitment of eosinophils into the skin, and the chemotaxis of cultured Alox15 −/− eosinophils towards CCL11/eotaxin-1 is compromised. Finally, we demonstrate that 15-lipoxygenase-1, the human homologue of 12/15-LO is induced in granulocytes in lesional skin of patients suffering from a pemphigoid disease. Collectively, our result uncover key mechanisms resolving IgG-mediated skin inflammation. These mechanisms are orchestrated by 12/15-LO expressed in eosinophils promoting the recruitment of eosinophils and Tregs, which in turn inhibit neutrophils. Graphical abstract: Image 1 Highlights: Resolution of autoantibody-mediated tissue inflammation is organized 12/15-lipoxygenase Eosinophils are the only site of 12/15-LO expression, making eosinophils key regulators of resolution. Intrinsic activity of 12/15-LO promotes eosinophil recruitment into sites of inflammation.